A novel planar wide‐angle scanning phased array under operation of TM10 and TM20 modes. Issue 3 (21st October 2020) - Guan, Lian‐Xu; Cheng, You‐Feng; Feng, Ju; Liao, Cheng
Abstract: A low‐profile planar phased array based on the hybrid‐mode patch technique is presented to achieve the goal of increasing the scanning angle. The array element antenna simultaneously operates at TM10 and TM20 modes of two rectangle patches. By adjusting the length of a slot etched on one patch, the far field of the two modes can be combined by a certain proportion, and thus the complementary beams realize wide‐beam radiation. Besides, in order to improve the array active reflection performance in a wide‐scan range, the slot technique is adopted to achieve the element miniaturization, and a grounded isolator is introduced to reduce the mutual coupling between the array elements. The proposed phased array shows a measured main‐beam coverage from −68° to +66° with its gain fluctuation and sidelobe levels lower than 1.5 and − 10 dB, respectively.